2014
DOI: 10.1039/c3ja50313e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the nitrogen abundance in organic materials by NanoSIMS quantitative imaging

Abstract: We describe a procedure to determine precise and accurate elemental abundance by means of quantitative imaging using secondary ion mass spectrometry (on images covering $10 Â 10 mm 2 ) applied to natural Insoluble Organic Matter (IOM). Dynamic SIMS conditions are reached for a 16 keV Cs + fluence of >2.0 Â 10 17 Cs + cm À2 implanted at the surface of the IOM. Once the sample surface is saturated in cesium, steady-state implantation and sputtering yield are reached: constant secondary ion count rates are then o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 38 publications
(55 reference statements)
4
50
0
Order By: Relevance
“…The observed relationship -α N = 9.8051 × N/ C + 0.0029 -is equivalent to those previously determined by Nano-SIMS on flattened OM (Thomen et al, 2014;Alleon et al, 2016). This is consistent with a wealth of literature data showing that the determination of the N/C atomic ratio in situ is not biased by matrix effects (Van Zuilen et al, 2007;Thomen et al, 2014;Alleon et al, 2016;Delarue et al, 2017).…”
Section: Nanosims Analysessupporting
confidence: 77%
See 4 more Smart Citations
“…The observed relationship -α N = 9.8051 × N/ C + 0.0029 -is equivalent to those previously determined by Nano-SIMS on flattened OM (Thomen et al, 2014;Alleon et al, 2016). This is consistent with a wealth of literature data showing that the determination of the N/C atomic ratio in situ is not biased by matrix effects (Van Zuilen et al, 2007;Thomen et al, 2014;Alleon et al, 2016;Delarue et al, 2017).…”
Section: Nanosims Analysessupporting
confidence: 77%
“…In parallel, it has been demonstrated that the emission of secondary ionic species used to monitor elements such as C or N can also be quantitatively associated with the geochemical elemental composition of both bulk OM (Thomen et al, 2014;Alleon et al, 2016) and individual organicwalled microfossils (Oehler et al, 2009(Oehler et al, , 2010Delarue et al, 2017). For instance, the 12 C 14 N − / 12 C 2 − secondary molecular ion ratio allows the determination of the N/C atomic ratio (Thomen et al, 2014), which is often used as a proxy for OM degradation during early diagenesis (Watanabe et al, 1997;Beaumont and Robert, 1999). However, the quantitative capabilities of NanoSIMS have been little used since some analytical biases may significantly alter 12 C 14 N − and 12 C 2 − emissions.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations